Introduction: Lebensraum and its discontents - Klinke, I; Bassin, M (Elsevier, 2018)
This introductory essay sets up the discussion in this special section on the first English language translation of Friedrich Ratzel's 1901 Lebensraum essay. After providing biographical context for this controversial nineteenth-century German geographer, we offer a brief history of what is perhaps his most famous conceptual contribution: Lebensraum (living space). We end by introducing the five contributions to this special section.